Biomimetic synthesis of novel calcium carbonate heterogeneous dendrites. (12th May 2015) - Ma, Li; Zhu, Jianhua; Cui, Mingfang; Huang, Lei; Su, Yiping
Abstract : Three-dimensional dendrites of calcium carbonate were successfully synthesized via a nonclassical crystallization pathway by combining two different functional additives. They showed fascinating heterogeneous superstructures made up of calcite scaffolding, aragonite shells, and an external amorphous coating. Abstract : Calcium carbonate dendrites with novel leaf- and snowflake-like morphology were synthesized with the combination of two different functional additives. They show fascinating heterogeneous domains made up of internal calcite scaffolding, aragonite shell and external amorphous calcium carbonate coating. They were formed in a gel-like solution composed of an amorphous or liquid-like mineral precursor. The developing dendrites arose from the correlation of solute diffusion and the driving force of crystallization. Their heterogeneous microstructures were determined by the balance between thermodynamic and kinetic reactions. Our research provided a novel procedure towards the formation of heterogeneous inorganic superstructures with the synergistic effects of two different additives.